PENGARUH HUKUMAN (PUNISHMENT) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI MTS NAHDLATUL ARIFIN SUMBEREJO AMBULU - NUR MUHAMAD IKBALILMAROM (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The application of punishment (punishment) at MTs Nahdlatul Arifin is still the main reference for controlling student attitudes at school. This has a lot of influence on the students themselves and can even affect student learning outcomes, especially in social studies subjects. This study uses a quantitative approach with the type or design of research ex post facto (from after the fact). The population in this study were students at MTs Nahdlatul Arifin Sumberejo Ambulu. In the sampling using the formula of Issaq and Michel. Meanwhile, the data collection method used a questionnaire, observation, documentation and legger of students' PAT scores. The data obtained were then carried out descriptive tests and statistical tests using